Determinants of chronic otitis media with effusion in preschool children: a case–control study. Issue 1 (December 2017) - Walker, Rebecca; Bartley, Jim; Flint, David; Thompson, John; Mitchell, Edwin
Abstract Background Chronic otitis media with effusion (COME) is a prevalent upper airway infection resulting in hearing loss. The aim of this research was to determine risk factors for COME in preschool children. Methods A case–control design was conducted in Auckland, New Zealand from May 2011 until November 2013. The cases were children aged 3 and 4 years referred for tympanostomy tube placement due to a diagnosis of COME (n  = 178). The controls were a random sample of healthy children aged 3 and 4 years from primary care practices (n  = 209). The children's guardians completed an interviewer-administered questionnaire that covered topics including socio-demographic information, pregnancy and birth, infant feeding practices, home environment, and respiratory health. In addition, skin prick tests for atopy were performed. Odds ratios (OR) estimating the risk of COME independently associated with the exposures were calculated using a logistic regression model. Results Children with COME frequently had nasal obstruction (OR: 4.38 [95% CI: 2.37–8.28]), always snored (OR: 3.64 [95% CI: 1.51–9.15]) or often snored (OR: 2.45 [95% CI: 1.04–5.96]), spent more hours per week in daycare (OR per hour/week: 1.03 [95% CI: 1.00–1.05]), had frequent colds (OR: 2.67 [95% CI: 1.59–4.53]), had siblings who had undergone tympanostomy tube placement (OR: 2.68 [95% CI: 1.22–6.02]), underwent long labour (OR: 2.59 [95% CI: 1.03–6.79]), and had early introduction of cow's milk (OR: 1.76 [95% CI: 1.05–2.97]). Asian ethnicity (OR: 0.20 [95% CI: 0.07–0.53]) and having older siblings (OR: 0.54 [95% CI: 0.31–0.93]) were inversely associated with COME. Conclusion COME in preschool children was associated with pathogen exposure, respiratory infection, and nasal obstruction. Strategies to prevent pathogen transmission warrant investigation. The novel findings of long labour and early cow's milk introduction require replication in future studies.